Tinjauan Hukum Ekonomi Syari’ah: Take Over Pembiayaan Mikro Bank Syari’ah - Nurasikin, Akhmad; Handayani, Tri; Rahman, Arif; Fatmawati, Siti Selviyah (Universitas Wahid Hasyim Semarang, 2021)
Although Indonesia is still facing formidable challenges due to the Covid-19 pandemic, the distribution of financing in the MSME sector and the micro segment continues to increase.